Evaluation of environmental health benefits of China's building energy conservation policies: an integrated assessment on national and provincial levels. Issue 3 (4th May 2018) - Yang, Xi; Xi, Xiaoqian; Lin, Wanqi; Guo, Shan; Feng, Xiangzhao; Gilmore, Elisabeth
Abstract: This article evaluates the effect of energy conservation policies and carbon mitigation efforts on reducing health damage in China's building sector, which has been long ignored. The study bases on both national and provincial levels. To evaluate the health damage effect, we use domestic data by region to ensure the reliability of the evaluation. Results show that in the co-control scenario, the GDP loss saved from health benefit in 2020, 2030, and 2050 is 0.13 %, 0.16 %, and 0.23 %, respectively, compared to reference scenario. At a provincial level, extra health benefit of 16, 16, 33, 25, and 23 RMB/person can be observed for Beijing, Heilongjiang, Guangdong, Henan, and Qinghai owing to energy conservation, even with the strictest end-of-pipe control measures. The results confirm the significant effect of energy conservation efforts on reducing the health damage in China's building sector at both national and provincial levels.